Muthawif concessions in Umrah travel bureau management - Fallah, Afanin Atiqa; muhajarah, kurnia (Universitas Islam Indonesia, 2024)
IntroductionIn Indonesia, the demand for Umrah services has grown significantly, amplifying the need for skilled muthawif who can support pilgrims both spiritually and logistically. The unique position of muthawif within the Umrah travel ecosystem requires well-structured management to ensure that service quality meets pilgrims' expectations. This study addresses the gaps in understanding how muthawif management practices are implemented within Indonesian travel bureaus and identifies the role of Saudi concessions in shaping these practices.ObjectivesThe primary objectives of this study are to assess the responsibilities of muthawif within the framework of concessions provided by Saudi and Indonesian authorities and to analyze the management approaches that optimize muthawif roles in enhancing the pilgrim experience. This research also seeks to identify the operational challenges faced by muthawif in balancing their duties across various management structures.MethodA qualitative field research approach was adopted, involving interviews and observations with key stakeholders such as muthawif, Umrah bureau directors, and agency leaders. Data was collected in both Indonesia and Saudi Arabia, allowing for an in-depth exploration of how muthawif function within different organizational and regulatory contexts. This approach provides contextual insights into the management practices influencing muthawif performance.ResultsThe study found that muthawif in Indonesia operate within three main categories: government-managed, agency-affiliated, and freelance. Each type of muthawif has different levels of flexibility and operational scope, impacting the quality and consistency of guidance services. Saudi government concessions offer operational flexibility, while Indonesian travel bureaus emphasize standardized training and service quality aligned with Islamic principles. These differences impact how muthawif adapt to the needs of diverse pilgrim groups.ImplicationsThe findings suggest that structured management and regulatory concessions are crucial to enhancing muthawif performance and service quality. Collaborative efforts between Indonesian travel bureaus and muthawif agencies contribute to a more professional and efficient Umrah guidance service. This study provides practical insights for travel bureaus and policymakers seeking to improve muthawif training standards and management practices within the Umrah industry.Originality/NoveltyThis research expands the literature on Umrah service management by focusing on the specific roles and concessions governing muthawif. It introduces new perspectives on optimizing muthawif performance through coordinated management approaches and cross-agency collaboration, addressing a critical area of service quality for Indonesian pilgrims undertaking Umrah.